KEPELBAGAIAN KAEDAH PUNGUTAN ZAKAT: ANALISIS DI PUSAT PUNGUTAN ZAKAT-MAJLIS AGAMA ISLAM WILAYAH PERSEKUTUAN DARI TAHUN 2003-2009: Diversity in Zakat Collection Methods: An Analysis of the Zakat Collection Centre of the Federal Territory Islamic Religious Council for 2003-2009 - Muhammad, Fidlizan; Mohd Hussin, Mohd Yahya; Awang, Salwa Amirah; Mohamed, Abdul Majid Tahir (Jurnal Syariah, 2012)
This article aims to analyse the zakat payment method implemented by the Pusat Pungutan Zakat – Wilayah Persekutuan (PPZ-MAIWP). Based on data from 2003 to 2009, PPZ-MAIWP has recorded a positive trend of total annual zakat collection. This increasing trend was driven by the PPZ-MAIWP initiative to implement a variety of payment mechanisms in line with the needs and technological change. Thus, their initiatives can become a model to other charity institutions. Furthermore, it will also provide opportunities and facilitate Muslims in Malaysia fulfilling the Islamic pillars.